Divide et Impera: Negotiating with a Stakeholder - Paola Manzini (Institute for the Study of Labor (IZA), 2002)
In many kinds of bilateral negotiations the resolution of the issues at stake has an impact which extends beyond the remits of the parties directly involved (e.g. labour negotiations in sectors of public interest, where a strike would impact on the public at large). Once this is recognised, negotiations ought to account for the interests of such stakeholder, whose stake is linked to the original negotiations. This interplay of different interests may introduce a strategic incentive to delay agreement in order to win the maximum concessions from one's opponents.
Keywords: J5; C7; D74; 330; Stakeholders; bargaining; war of attrition; Verhandlungstheorie; Konflikt; Lohnverhandlungen; Öffentliches Interesse; Theorie